2010
DOI: 10.1002/cncr.25246
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intensity‐modulated radiotherapy and 3‐dimensional conformal radiotherapy as adjuvant therapy for gastric cancer

Abstract: BACKGROUND:The current study was performed to compare the clinical outcomes and toxicity in patients treated with postoperative chemoradiotherapy for gastric cancer using intensity-modulated radiotherapy (IMRT) versus 3-dimensional conformal radiotherapy (3D CRT). METHODS: Fifty-seven patients with gastric or gastroesophageal junction cancer were treated postoperatively: 26 with 3D CRT and 31 with IMRT. Concurrent chemotherapy was capecitabine (n ¼ 31), 5-fluorouracil (5-FU) (n ¼ 25), or none (n ¼ 1). The medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 20 publications
5
70
0
Order By: Relevance
“…Although IMRT does not provide a significant reduction in acute toxicity compared to con RT, it does spare the kidneys and liver, as demonstrated in this study as well as previous studies [11][12][13]. The sparing of critical organs is clinically very important because concurrent chemotherapy also affects the kidneys, liver, and parts of the spinal cord and because it reduces potential long-term toxicity, especially for patients undergoing major abdominal surgery and for those who may subsequently need further chemotherapy.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Although IMRT does not provide a significant reduction in acute toxicity compared to con RT, it does spare the kidneys and liver, as demonstrated in this study as well as previous studies [11][12][13]. The sparing of critical organs is clinically very important because concurrent chemotherapy also affects the kidneys, liver, and parts of the spinal cord and because it reduces potential long-term toxicity, especially for patients undergoing major abdominal surgery and for those who may subsequently need further chemotherapy.…”
Section: Discussionsupporting
confidence: 58%
“…A previous comparison of patients treated with con RT or IMRT indicated that IMRT reduces the dose to the liver but does not reduce acute gastrointestinal toxicity [11]. This finding was supported by another study in which IMRT was also shown to provide better protection of the liver and kidneys compared with 3D CRT [12], although this conflicts with a study that showed only marginal sparing of the kidneys [13].…”
Section: Discussionmentioning
confidence: 93%
“…Subsequently, consensus guidelines were published to review important anatomic issues to be considered to ensure that radiation oncologists understood the location of the intended targets [45,46]. Current studies are exploring the benefits of transcending the two-dimensional techniques used in the INT-0116 study in favor of three-dimensional conformal and intensity-modulated radiation therapy [47,48]. These techniques rely on computed tomography (CT)-based treatment planning to maximize dose to the intended regions and minimize dose to the surrounding normal tissues.…”
Section: Discussion: Is Radiation Really Necessary?mentioning
confidence: 99%
“…All patients received effective supportive care, especially nutritional support, which was very important to maintain the tolerability of the patients for the combined treatments. In the setting of definitive chemoradiotherapy, image guided 3D-CRT and IMRT are warranted to appropriately protect the critical organs around the tumor, including small intestines, kidneys, liver and the spinal cord [20]. Typically the target volumes include gross tumor, nodal regions and structures at risk of involvement.…”
Section: Discussionmentioning
confidence: 99%